Le guide musical : revue hebdomadaire des nouvelles musicales de la Belgique et de l'étranger - Schott, Peter Bernhard (Brussels Sannes, 1870)
Le Guide musical (English: The Music Guide) was a French-language Belgian and French classical music periodical founded 1 March 1855 in Brussels by Peter Bernhard Schott (18211873), of the Brussels music publishing house Schott frères (Schott brothers)
Keywords: Music criticism